LANDSLIDE DISASTER RISK REDUCTION STRATEGY BASED ON COMMUNITY EMPOWERMENT (Case Study in Kuta Cot Glie District, Aceh Besar District) - Nurul Rizki; Sulastri; Marty Mawarpury (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Lamkleng Village, Kuta Cot Glie District, is located in the Selawah valley area of Aceh Besar, which is a landslide-prone area. So far there has been no effort to reduce disaster risk that has been carried out optimally. This study aims to obtain alternative strategies for reducing the risk of landslides based on community empowerment in Lamkleng Village, Kuta Cot Glie District, Aceh Besar. This research uses a qualitative approach (action research). In this study using a qualitative descriptive method, using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), and using QSPM (Quantitative Strategic Planning Matrix) analysis. The results of this study are the social conditions of the people of Lamkleng Village, Kuta Cot Glie District, Aceh Besar as farmers and traders.